(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
In times of globalization, infectious diseases possess a transboundary dimension and are a common concern that require State cooperation. The CoViD-19 pandemic – which hit every country in the world – has raised several doubts on the efficiency of global health governance. In particular, the WHO Director-General Tedros Adhanom Ghebreyesus faced criticism for his presumed strategy to appease China. Against this backdrop, I will argue that the pandemic has shed light on the weaknesses of global health law. Why States’ preparedness to the coronavirus was so inefficient? Why neither WHO, neither its Member States have reacted to the evident China’s violations of international law (in particular the duties to share epidemiological data, duty of early warning and the obligation to avoid transboundary harm)? Why the WHO Emergency Committee had decided at first not to declare a public health emergency? This paper explains the role of WHO Director-General in responding to the CoViD-19 outbreak within the broader context. It will evaluate, in particular, which are the implications of the CoVid-19 Pandemic Declaration for health governance, its legal scope, and its contribution to the exercise of International Public Authority by WHO.